Anti‐Inflammatory Effects of a Vegan Diet Versus the American Heart Association–Recommended Diet in Coronary Artery Disease Trial - Shah, Binita (J Am Heart Assoc, 2018)
BACKGROUND: Dietary interventions may play a role in secondary cardiovascular prevention. hsCRP (High‐sensitivity C‐reactive protein) is a marker of risk for major adverse cardiovascular outcomes in coronary artery disease. METHODS AND RESULTS: The open‐label, blinded end‐point, EVADE CAD (Effects of a Vegan Versus the American Heart Association‐Recommended Diet in Coronary Artery Disease) trial randomized participants (n=100) with coronary artery disease to 8 weeks of a vegan or American Heart Association–recommended diet with provision of groceries, tools to measure dietary intake, and dietary counseling. The primary end point was high‐sensitivity C‐reactive protein. A linear regression model compared end points after 8 weeks of a vegan versus American Heart Association diet and adjusted for baseline concentration of the end point. Significance levels for the primary and secondary end points were set at 0.05 and 0.0015, respectively. A vegan diet resulted in a significant 32% lower high‐sensitivity C‐reactive protein (β, 0.68, 95% confidence interval [0.49–0.94]; P=0.02) when compared with the American Heart Association diet. Results were consistent after adjustment for age, race, baseline waist circumference, diabetes mellitus, and prior myocardial infarction (adjusted β, 0.67 [0.47–0.94], P=0.02). The degree of reduction in body mass index and waist circumference did not significantly differ between the 2 diet groups (adjusted β, 0.99 [0.97–1.00], P=0.10; and adjusted β, 1.00 [0.98–1.01], P=0.66, respectively). There were also no significant differences in markers of glycemic control between the 2 diet groups. There was a nonsignificant 13% reduction in low‐density lipoprotein cholesterol with the vegan diet when compared with the American Heart Association diet (adjusted β, 0.87 [0.78–0.97], P=0.01). There were no significant differences in other lipid parameters. CONCLUSIONS: In patients with coronary artery disease on guideline‐directed medical therapy, a vegan diet may be considered to lower high‐sensitivity C‐reactive protein as a risk marker of adverse outcomes. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT02135939.